Organizing Decision-Making Support System Based Multi-Dimensional Analysis of the Educational Process Data - N. Beridze; G. Janelidze (Journal of ICT, Design, Engineering and Technological Science, 2020)
It is important to make right and immediate decisions on the management of the education process and introduce quick decision-making support systems, which will increase the demand for academic attendance analysis, which is impossible without regular monitoring of the data. All the above-mentioned requires a comprehensive approach to the process management and appliance of modern instruments and informational technologies. The current work discusses the decision-making support systems' architecture, which includes three main components: data storage server, data collection, analysis instruments, and labour market research methodologies. Based on the analysis of the received data from the monitoring of teaching and study, the data warehouse and Online Analytical Processing (OLAP) technology are used. OLAP cube enables us to visualize, make statistical analysis, and study data. In the decision-making process solution, the problem of achieving the qualitative compliance of the professional potential and vacancies available on the labour market has an important role. The most important approach is organizing a market-oriented, flexible, and re-arranging education system out of suggested solutions. The approach provided in work will support education quality assurance service to identify trends, problems, achievement promptly to organize decision-making to improve the education process. The analysis based on the data received from the study and teaching monitoring is presented for which the data storage and OLAP (Online Analytical Processing) technology are applied. OLAP cube enables to visualize data, make statistical analysis and study data. The paper presents the problems related to the correspondence of professional potential and the vacancies available on the labour market during the decision-making process and solution ways. The most important thing is to organize a market-oriented, flexible, easy re-constructible education system.